The Analysis of Satire in Stand Up Comedy Indonesia (Suci) 8 Kompas TV - Afrina Nanda Jaya; Bukhari Daud; Lismalinda Lismalinda (Universitas Syiah Kuala, 2022)
This research deals with satire in Stand Up Comedy Indonesia (SUCI) 8. The objectives of this study were to find out the types of satire which were applied in Stand Up Comedy Indonesia (SUCI) 8 based on Abrams’ and Harphams’ theory and the differences betweeen the use of types of satire to the age group of the speaker on the 10 performances. This research applied a qualitative method. The subject of this research was the “Stand Up Comedy Indonesia (SUCI) 8” and types of satire also the differences that found as the object. The findings of this research shows that there were three types of satire found in this research, they were Juvenalian, Horation, and Manippean Satire. It found 17 utterences consist of satire, there were Juvenalian 5 utterences, Horation 10 utterances, and Manippean 2 utterances. Horation was the most dominat types found in this research. Whereas for the differences betweeen the use of types of satire to the age group of finalist on the 10 performances, it found that there were no any differences in using types of satire despite the age difference among the finalists. As further recommendation, the researcher is expect there will be another research about analyzing satire in other literary works or the next edition of SUCI.